Valıdıty And Effıcacy Of The Lapse Termınatıon Petıtıon Post Constıtutıonal Court Decısıon Number: 102/PUU-XII/2015 And Supreme Court Cırcular Letter Number: 5 Of 2021 Regardıng The Implementatıon Of The Formulatıon Of The Results Of The Pleno Meetıng Of - Irza Winasis; I Nyoman Nurjaya; Prija Djatmika (Cita Konsultindo Research Center, 2024)
This study examines the issue of the term of dismissal of pretrial applications after the Constitutional Court decision Number: 102 / PUU / -XII / 2015 and Supreme Court Circular Number: 5 of 2021 concerning the Implementation of the Formulation of the Results of the Supreme Court Chamber Meeting in terms of validity and enforceability. This research was motivated by the blurring of norms governing the termination of pretrial applications as in Article 82 paragraph (1) letter d of the Code of Criminal Procedure which states that pretrial deaths are when the main case has begun to be examined by the district court. This research uses normative juridical research methods and uses the Statute Approach, Conceptual Approach, and Historical Approach. The results of this study found that the Constitutional Court has validity in deciding cases as case Number: 102 / PUU / -XII / 2015 and the appeal is valid to be issued by the Constitutional Court. The Supreme Court also has validity in issuing Supreme Court Circular Number: 5 of 2021 concerning the Implementation of the Formulation of the Results of the Meeting of the Supreme Court Chamber related to the regulation of the term for the termination of pretrial applications. After the decision of the Constitutional Court and the Supreme Court Circular, based on the decision of the court handling pretrial application cases, it is the Supreme Court Circular that is currently in force or guided by the examining judge of pretrial cases on the basis that the Supreme Court Circular has legal certainty compared to the Constitutional Court Decision regarding the term for the termination of pretrial applications.